Observations of HO(x) Radical in Field Studies and the Analysis of Its Chemical Mechanism - Lu, K. D.; Zhang, Y. H. (Progress in ChemistryProgress in Chemistry, 2010)
Researches on HO(x) radical chemistry would provide theoretical support for understanding the global climate change and regional air pollution control. At present stage, comprehensive field campaign including HO(x) radial measurements is one of the critical approaches to advance it. However, due to the very short lifetime and extremely low concentration of HO(x) in the atmosphere, direct measurement of HO(x) radical is one of most challenged works in atmospheric chemistry. This paper reviews the direct measurement techniques of the HO(x) radical, summarizes the observed dynamics range of its concentrations, introduces the current schematic diagram of the HO(x) radical chemistry and the important contributions from previous field studies, and discusses the main scientific questions that need further researches. Besides, the progress of the HO(x) radical chemistry in China is reviewed, and several potentially important research directions are pointed out.